A critical assessment of the Archimedes density method for thin-wall specimens in laser powder bed fusion: Measurement capability, process sensitivity and property correlation. (July 2022) - Bruce, Daniel; Paradise, Paul; Saxena, Anushree; Temes, Samuel; Clark, Ryan; Noe, Cameron; Benedict, Mark; Broderick, Thomas; Bhate, Dhruv
Abstract: The Archimedes method is a commonly used approach for measuring the density of specimens fabricated with metal additive manufacturing. Most of the specimens fabricated for this purpose are cubes with 10 mm sides. This work examines the appropriateness of using the Archimedes method for estimating the density of thin-wall specimens (0.3–2 mm thick). The significantly higher surface area to volume ratio of these specimens, as well as their cumbersome size, can introduce measurement challenges not seen for the standard cubic specimens. The method is assessed for thin-walls in three ways: first, a Measurement Capability Analysis is conducted, quantifying repeatability and reproducibility and comparing them to those obtained for cubic specimens. Then, densities are assessed for their sensitivity for detecting differences due to changes in thickness, post-processing conditions (Hot Isostatic Pressing, or HIP) and build location. Finally, density values are correlated to mechanical tensile test metrics to establish trends and R 2 values. The Archimedes method is shown to be capable of measuring thin wall densities for specimens as thin as 0.3 mm, though standard deviation is shown to increase as thickness reduces. The method is also sensitive enough to detect differences due to thickness and HIP, and to a lesser extent, build location. Finally, densities obtained from this method yield interesting insights for modulus, ultimate tensile strength and elongation, with R 2 values in some cases exceeding 0.6. This work focuses on Inconel 718 tensile test specimens fabricated using the laser powder bed fusion process and demonstrates that the Archimedes method is a capable and critical tool in developing thin wall structures.